SAT0469 "interstitial lung disease in idiopathic inflammatory myopathies: ultrasound assessment of pleural irregularities and comparison with high resolution computed tomography". (12th June 2018) - Cioffi, E.; Barsotti, S.; Romei, C.; Giovanetti, C.; Roncella, C.; Ferro, F.; Perrone, E.; Mosca, M.; Falaschi, F.; Neri, R.
Abstract : Background: Interstitial Lung Disease (ILD) is one of the most frequent and significant extra-muscular manifestations in Idiopathic Inflammatory Myopathies (IIM). Although high resolution computed tomography (HRCT) remains the gold standard technique for the evaluation of ILD, during the last years several authors proposed ultrasound (US) quantification of pleural irregularities (PIs) as a possible method to detect lung involvement in IIM patients. Objectives: The objective of our study was to evaluate the prevalence of PIs and to compare the results obtained to the data provided by HRCT. Methods: Thirtyseven patients (24 females, 13 males, mean duration of the disease 5.21±7.6 and median age 62.24±1.8 years) with a diagnosis of IIM according to Bohan and Peter criteria (17PM, 16DM, 1MCI, 3overlap syndromes) who required HRCT evaluation were enrolled. All patients underwent rheumatological clinical evaluation, including dyspnoea measurement by means MRC scale and disease activity assessment according to IMACS criteria (muscle enzymes, MMT8, VAS, HAQ, MYOACT). Patients were also asked to complete Patient Reported Outcome (PRO) questionnaires as Leicester Cough Questionnaire (LCQ). All the patients underwent a thoracic US evaluation in 53 anterior and posterior thoracic areas by Esaote MyLab Gold ultrasound device with 8–18 MHz linear probe. We evaluated the aspect of the pleural profile assigning each space a score according to a 3 points scale (regular=0, mild irregularity=1, irregularity=2) and summed the score in each space to obtain the PIs total score. HRCT was assessed by an expert radiologist to obtain a semiquantitative evaluation of parenchymal involvement by Warrick score. In a subgroup of patients, thoracic US was repeated by the same operator after two days from the first evaluation and by a second operator to valuate the intrareader and interreader agreement of the technique. Results: The PIs total score obtained with lung US (24.70±13.66) was higher in patients with thoracic crackles at clinical examination (p=0.008) and in patients with positivity for antisynthetase autoantibodies, particularly anti-Jo1 (p<0.001). A positive correlation was found between PIs total score and MYOACT total score ( r =0.36;p = 0.027), instead a negative one was found with LCQ score( r =-0, 56; p=0, 009). Interestingly, a good correlation between PIs total score and the Warrick score (r=0.65;p<0.001) was found. From the analysis of ROC curve, we demonstrated that a cut-off of PIs total score <18.5 might be able to identify all patients with HRCT abnormalities (sensitivity 100%). Lung US was repeatable (inter-reader reliability: α =0.916) and reproducible (intra-reader reliability: α =0.945). Conclusions: The US PIs total score is strictly correlated to clinical, serological and HRCT parameters and as the lung US is a non-invasive and relatively inexpensive technique, the results of our study suggest a possible role of this method in the screening of lung involvement in IIM patients. Follow up studies in a larger cohort of IIM patients are required. Disclosure of Interest: None declared